2022
DOI: 10.1016/j.scitotenv.2021.150495
|View full text |Cite
|
Sign up to set email alerts
|

Laundering of face masks represents an additional source of synthetic and natural microfibers to aquatic ecosystems

Abstract: From the onset of Covid-19 pandemic, the use of face masks has been adapted as one of the main measures to slow down the transmission of the SARS-CoV-2 virus worldwide. The inadequate handling and management of face masks lead to a massive dispersal in the environment, resulting in a new source of microfibers because of their breakdown and/or degradation. In addition, the laundering of reusable face masks of different polymeric composition can represent an additional sources of microfibers to natural ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The measured static water contact angles are presented in Table S2 , where it could be observed that all contact angles measured for the distinct layers of all non-processed (control) masks were well above 90° (between 115.4° and 151.3°, for PP-based layers, and 132.9°, for the only PET-based layer). This indicates as expected that all the layer materials employed in these RPD originally presented a high hydrophobic nature [ 25 , 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The measured static water contact angles are presented in Table S2 , where it could be observed that all contact angles measured for the distinct layers of all non-processed (control) masks were well above 90° (between 115.4° and 151.3°, for PP-based layers, and 132.9°, for the only PET-based layer). This indicates as expected that all the layer materials employed in these RPD originally presented a high hydrophobic nature [ 25 , 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 75%
“…As mentioned above, the studied decontamination treatments may affect some of the polymeric materials’ morphological properties, namely porosity, average pore diameters, fibre densities and fibre charges of the distinct layers that comprise the RPD, affecting the safety, efficiency and other functional and comfort-related properties of these types of protective devices [ 25 , 29 , 35 , 41 , 51 ]. In this context, mercury intrusion results ( Figure S3 ) showed that after 10 treatment cycles using the H 2 O 2 , NaClO and steam bag treatments, only relatively small variations were observed for the overall porosity (%) and median pore sizes of the original RPD ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microfibers shed easily from this type of mask, similar to the release of polyester fibers from textiles during laundry ( Rathinamoorthy and Balasaraswathi, 2021 ). Importantly, it has been estimated that microfibers released from face masks range between 284.9 and 823 particles per wash ( De Felice et al, 2022 ). While most studies overlook the smaller components of PPE, here we identified PET and PA as the main composition of the elastic cords in two face masks, similar to the report by Shen et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Although reusable masks can reduce the overall wastage, microfibers released after cleansing the mask diffuse into the aquatic environment [ 36 ]. There have been more discussions on the sustainability of reusable masks [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ].…”
Section: Methodsmentioning
confidence: 99%